Clio and Computers in Canada and Beyond: Contested Past, Promising Present, Uncertain Future. - Gaffield, Chad (Canadian Historical Review, 2020)
Historians began using computers in the 1950s and 1960s when their possibilities seemed unlimited in the private, public, and non-profit sectors of wealthier countries. In this societal context, Clio met computers. In the following decades, a few historians would predict, from time to time, that digitally-enabled scholarship was on track to become the disciplinary norm. They emphasized the impact of specific initiatives enabled by changing technologies, from the mainframe era to microcomputers, the web, the tsunami of "born-digital" and digitized data, mobile devices, and new computational approaches such as machine learning. However, their predictions routinely failed to materialize and, while all historians might use digital tools at least to some extent, a claim that "we-are-all-digital-now" downplays substantive questions about History's past and current relationship with new technologies. This article re-interprets the changing meaning of digital technologies within the disciplinary culture and institutional conditions of History. The evidence thus far reveals good reasons for both optimism and pessimism about digitally-enabled History at various times since the 1950s. By examining the complex and often surprising past and present, we can better determine and take the needed next steps in Digital History.